Thermal transport of magnetohydrodynamic electroosmotic flow in circular cylindrical microchannels. (April 2018) - Xie, Zhi-Yong; Jian, Yong-Jun; Li, Feng-Qin
Highlights: Magnetodydrodynamic electroosmotic flow is investigated through a circular microtube. The effects of Joule heating and viscous dissipation are considered. Non-dimensional temperature is numerically obtained. The variations of Nusselt number are discussed in detail. Abstract: Thermal transport phenomena of magnetohydrodynamic electroosmotic flow are investigated through a circular cylindrical microchannel. The fluid flow can be actuated by the interactions of imposed pressure-gradient, electroosmosis and additional electromagnetic field. Under the appropriate assumptions, the distributions of the non-dimensional flow velocity can be obtained. Based upon the achieved velocity field, heat transfer characteristics, explained by the non-dimensional temperature and Nusselt number, are discussed graphically by taking into account the effects of viscous dissipation and Joule heating under the constant wall heat flux circumstance. Concisely, the results show, in the absence of lateral electric field, the flow velocity decreases with the increasing magnitudes of Hartmann number resulting in the decrease of non-dimensional temperature, which ultimately culminates in increasing the Nusselt number. However, the profiles of non-dimensional flow velocity, non-dimensional temperature and Nusselt number are demarcated into two regions based on the value of critical Hartmann number and exhibit an adverse trend among different regions due to the existence of lateral electric field. The present endeavor can be utilized to design the exquisite and efficient electromagnetic devices, especially within a specific regime of thermal transport characteristics.